Prospective Comparative Study of Above Elbow Cast for Six Weeks Versus Above Elbow Converted to Below Elbow Cast After Three Weeks for Pediatrics Distal Forearm Fracture - KC, Saugat; Gupta, Hemant Kumar; Hamal, Raj Kumar (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Forearm fractures are common injuries and the approach to manage these in children is different than similar injuries in adults. Various methods of cast immobilization are done for the treatment of distal forearm fractures in children. The purpose of this study was to determine if above elbow cast (AEC) converted to below elbow cast (BEC) in three weeks are as effective as above elbow cast (AEC) in the treatment of the distal forearm fracture. Therefore, this study was conducted with the objective of evaluating and comparing the outcome of above elbow cast (AEC) with above elbow converted to below elbow cast (BEC) after three weeks for management of pediatrics distal forearm fracture. Methods This study was conducted in Department of Orthopedic Surgery in College of Medical Sciences-TH Bharatpur, Nepal from February 2016 to January 2017. Among sixty cases thirty were selected in AEC group and thirty in above elbow converted to below elbow cast group (AEC/BEC) by simple random sampling. All patients were followed up six months. Results Out of sixty patients in two groups, fifty-three made to all follow up. Twenty- eight of cases were AEC group and twenty-five were AEC/BEC group. All the cases had union at six weeks and twelve weeks follow up. There was statistically significant difference in limitation in pronation/supination. Conclusions AEC converted to BEC for six weeks is effective as AEC for six weeks in the treatment of distal third forearm fracture in children. AEC/BEC group patients have lesser degree of loss of supination/pronation movement.